(3bUjOI GdHQOIs - (3GdUfgGLj GdHhUjQj GdeUQj, CHh YHO Gddg, TQa GdOjf , eMeO Hf SYjO Hf MeGO Hf YHO Gddg, (B696 (3g`s
(3ChdgG (B:s
(3Cef JPcQ LjQGf HPj Sde (B*** (3eRLJ OeYG LQi ef ebdI HOe , Ce gHJ GdQjM ef JdbGA cGXeI (B*** (3hCheV GdHQb aj GdXdeGA ef CVes
(3BNQgG (B:s
(3eG QfMJ YPHGJ GdHGf QjM UHG hCWQH GdYjS MGOj GdYjS HGdfZe , Ke GdQVi Yf CHj HcQ hYf YeQ (B*** (3hYf Ydj hYKeGf Phj GdcQes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 139s
(3eYLe GdeDdajf(B: 3 / 317s
(3cTa GdXfhf(B: 2 / 1331s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs